A különböző lakóhelyi szegregáció típusok kialakulásának hálózati modellezése = Network modelling of the formation of the different residential segregation types - Szilágyi, Győző Attila (Közép-Európai Közlemények, 2017)
The residential segregation is a common occurrence in the big cities. Although the reasons of the segregation evolvement could be different, the pattems of the spatial separation are similar. The characteristics of spatial segregation structure are greatly átfeded by the comfort feeling of people living in the area, which is associated with the behaviour of people living in the immediate surroundings. In the case if somebody’s comfort feeling sank under a critical level because of the neighbours’ behaviours he moves írom the area if he can do it. Bút the possibility of moving is alsó influenced by the volume and locality of the ffee residences. Taken intő consideration these options it was examined in a cellular automate model during the research that besides different initial and behaviour parameters what kind of reactions are given by the populations, what kind of spatial segregation pattems could be formed in the model and what kind of dynamic characteristics the pattem formations have. The resulting segregation pattems show a big similarity to the known forms of the urban segregation. Based on the results of the model it could be specified what kind of initial, population and behaviour parameters can be associated to the reál segregation occurrences.